Effect of cooling regime on the residual performance of high-volume palm oil fuel ash concrete exposed to high temperatures - Abdul Awal, A.S.M.; Shehu, I.A.; Ismail, Mohammad (Elsevier, 2015)
This paper presents the experimental findings of a study on the effect of cooling method on the residual performance of concrete containing a high volume of palm oil fuel ash (POFA) exposed to high temperatures. In this study, concrete samples were made in which the ordinary Portland cement was replaced by 50%, 60% and 70% POFA. The test specimens were then thermally treated to elevated temperatures of 200, 400, 600 and 800 C in an electric furnace for a period of 1 h. The specimens were cured by air cooling or water cooling and examined for ultrasonic pulse velocity and changes in weight and residual compressive strength. At higher temperatures, the reduction in the ultrasonic pulse velocity of concrete was higher for all of the mixes. Along with the loss of weight, the residual compressive strength of concrete was also reduced. Of the two regimes, the air-cooling system exhibited better performance in recovering the structural properties of concrete containing a high volume of POFA.